Ultrasound Enhanced Structural Modification of Oil Palm Empty Fruit Bunch (OPEFB) Fiber/Poly(Lactic) Acid Composites - Akindoyo, John Olabode; Beg, M. D. H.; Suriati, Ghazali (2015)

(untitled)
Effective surface modification of natural fibers with little or no damage to the fibers had been a prominent challenge to natural fiber reinforced polymer composites. Alkali treatment had been a very efficient technique for fiber treatment. However, environmental concerns make it necessary to as much as possible reduce the concentration of alkali for any fiber treatment. In this study, ultrasonic treatment in an alkali medium of low concentration was used to modify the surface of oil palm empty fruit bunch (OPEFB) fibers. Surface morphology of fibers due to treatment was studied by scanning electron microscopy (SEM) while its structural changes were studied by Fourier transforms infrared spectroscopy(FTIR) and X-ray diffraction (XRD). Composites were fabricated from oil palm empty fruit bunch fiber and poly (lactic) acid (PLA) through extrusion followed by injection moulding. Characterization of composites was done by mechanical testing such as tensile and flexural. Composite structural analysis was done by XRD analysis. Result showed that treatment of OPEFB fibers with ultrasound offered great structural changes which produced composites with highly desirable properties.